The Role of Anxiety, Coping Strategies, and Emotional Intelligence on General Perceived Self-Efficacy in University Students - Morales-Rodríguez, Francisco Manuel; Pérez-Mármol, José Manuel (Frontiers in Psychology, 2019)
The main objective of the present research is to analyze the relationship of levels of self-efficacy and anxiety, coping strategies and emotional intelligence in Spanish university students. This study has a cross-sectional design. The global sample was composed of 258 university students recruited from three academic areas. Descriptive, bivariate and multivariate regression analyses were performed. Significant bivariate analysis showed a significant inverse correlation between self-efficacy and state anxiety (r= -0.340) and trait anxiety (r= -0.466). In addition, a direct correlation was found between self-efficacy and the coping strategies of problem solving (r= 0.312), emotional expression (r= 0.133), cognitive restructuring (r= 0.195), social withdrawal (r= 0.103) and coping with a situation (r= 0.303), as well as with the emotional intelligence dimensions of emotional clarity (r= 0.397) and repair mood (r= 0.347). Multivariate regression analysis showed that trait anxiety, problem solving, emotional expression, social withdrawal and emotional clarity were significantly related to the dependent variable, predicting the 39% of total variance on levels of general perceived self-efficacy. In conclusion, this paper contributes to a better understanding of the related factors to general perceived self-efficacy in undergraduate students.